Discussion Note: Complexity-Aware Monitoring (USAID, 2018)
This Discussion Note complements ADS 201 and outlines general principles and promising approaches for monitoring complex aspects of USAID development assistance. Complexity-aware monitoring is a type of complementary monitoring that is useful when results are difficult to predict due to dynamic contexts or unclear cause and-effect relationships. Key principles of the Program Cycle include applying analytic rigor, managing adaptively, and utilizing a range of approaches to achieve results. ADS 201.3.5.5 identifies three types of program monitoring – performance, context, and complementary. All USAID programming incorporates performance monitoring and should include context monitoring. Performance monitoring “is the ongoing and systematic collection of performance indicator data and other quantitative or qualitative information to reveal whether implementation is on track and whether expected results are being achieved.” Context monitoring is “[t]he systematic collection of information about conditions and external factors relevant to the implementation and performance of an operating units (OU’s) strategy, projects, and activities.” As stated in ADS 201.3.5.5, complementary monitoring may be used by missions and Washington OUs to complement performance and context monitoring in situations where results are difficult to predict due to dynamic contexts or unclear cause-andeffect relationships. This Discussion Note provides an explanation of when to use complementary monitoring approaches that are complexity-aware and summarizes the three principles of complexity-aware monitoring.